The high prevalence and impact of rheumatic heart disease in pregnancy in First Nations populations in a high-income setting: a prospective cohort study - Sullivan, E. A.; Vaughan, G.; Li, Z.; Peek, M. J.; Carapetis, J. R.; Walsh, W.; Frawley, J.; Rémond, M. G.W.; Remenyi, B.; Jackson Pulver, L.; Kruske, S.; Belton, S.; et al. (BJOG: An International Journal of Obstetrics & Gynaecology, 2019)
Objective: To describe the epidemiology of rheumatic heart disease (RHD) in pregnancy in Australia and New Zealand (A&NZ). Design: Prospective population-based study. Setting: Hospital-based maternity units throughout A&NZ. Population: Pregnant women with RHD with a birth outcome of ≥20 weeks of gestation between January 2013 and December 2014. Methods: We identified eligible women using the Australasian Maternity Outcomes Surveillance System (AMOSS). De-identified antenatal, perinatal and postnatal data were collected and analysed. Main outcome measures: Prevalence of RHD in pregnancy. Perinatal morbidity and mortality. Results: There were 311 pregnancies associated with women with RHD (4.3/10 000 women giving birth, 95% CI 3.9–4.8). In Australia, 78% were Aboriginal or Torres Strait Islander (60.4/10 000, 95% CI 50.7–70.0), while in New Zealand 90% were Māori or Pasifika (27.2/10 000, 95% CI 22.0–32.3). One woman (0.3%) died and one in ten was admitted to coronary or intensive care units postpartum. There were 314 births with seven stillbirths (22.3/1000 births) and two neonatal deaths (6.5/1000 births). Sixty-six (21%) live-born babies were preterm and one in three was admitted to neonatal intensive care or special care units. Conclusion: Rheumatic heart disease in pregnancy persists in disadvantaged First Nations populations in A&NZ. It is associated with significant cardiac and perinatal morbidity. Preconception planning and counselling and RHD screening in at-risk pregnant women are essential for good maternal and baby outcomes. Tweetable abstract: Rheumatic heart disease in pregnancy persists in First Nations people in Australia and New Zealand and is associated with major cardiac and perinatal morbidity.